Feelings and Ethics Education: The Film Dear Scientists - Ioanna Semendeferi (American Society for Microbiology, 2014)
There is an increasing body of evidence that not only cognition but also emotions shape moral judgment. The conventional teaching of responsible conduct of research, however, does not target emotions; its emphasis is on rational analysis. Here I present a new approach, ‘the feelings method,’ for incorporating emotions into science ethics education. This method is embodied in Dear Scientists, an innovative film that combines humanities with arts and works at the subconscious level, delivering an intense mix of music and images, contrasted by calm narration. Dear Scientists has struck a chord across the science, humanities, and arts communities—a promising sign.